1996
DOI: 10.1001/archsurg.1996.01430240057007
|View full text |Cite
|
Sign up to set email alerts
|

Dominance of T-Helper 2–Type Cytokines After Severe Injury

Abstract: These data indicate that a shift to a Th2-type splenocyte cytokine response occurs late, at 7 days after injury. Modulation of Th cell cytokine responses may partially explain defects observed in cellular immune responses in postinjury states. Therapies that augment Th1-type cytokine production and/or neutralize Th2-type cytokines may prove beneficial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
65
1
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(73 citation statements)
references
References 32 publications
6
65
1
1
Order By: Relevance
“…On admission the mean age of the trauma patients ( n = 31) was 32·8 (range, 18-59), the mean ISS was 32·0 (17-59), APACHE II score of 13·5 (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) and mean GCS of 8·7 (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). There were 25 men and six women.…”
Section: Resultsmentioning
confidence: 99%
“…On admission the mean age of the trauma patients ( n = 31) was 32·8 (range, 18-59), the mean ISS was 32·0 (17-59), APACHE II score of 13·5 (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) and mean GCS of 8·7 (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). There were 25 men and six women.…”
Section: Resultsmentioning
confidence: 99%
“…Next, we wanted to determine whether burn-injured mice exhibit a similar difference in mortality if challenged with the same doses of these SAg at 7 days after injury, a time point when injured mice are know to express a Th2 phenotype (8,10,25). We found that burn-injured mice did not die when given either SEA or SEB at 7 days after burn injury at doses that were fatal at 1 day after injury.…”
Section: Discussionmentioning
confidence: 99%
“…eosinophils vs. neutrophils) Summaries of the T-helper cytokine response and its role in inflammation are available in the literature (Cameron et al, 2001;DiPiro, 1997;Miller et al, 2007). As a third cytokine-dependent mechanism, the cytokine milleu of CARS is also characterized by an upregulation of T H 2 cytokine responses (Mack et al, 1996). This upregulation of T H 2 cytokines serves to blunt the T H 1-dominant SIRS response through the modulation of leukocyte gene expression.…”
Section: Early Phase Cars: Suppressor Cells and Immunosuppressive Cytmentioning
confidence: 99%